Interactions between Nitrogen and Silicon in Rice and Their Effects on Resistance toward the Brown Planthopper Nilaparvata lugens - Wu, Xiaoying; Yu, Yaoguang; Baerson, Scott R.; Song, Yuanyuan; Liang, Guohua; Ding, Chaohui; Niu, Jinbo; Pan, Zhiqiang; Zeng, Rensen (Frontiers in Plant Science, 2017)
Nitrogen (N) and silicon (Si) are two important nutritional elements required for plant growth, and both impact host plant resistance toward insect herbivores. The interaction between the two elements may therefore play a significant role in determining host plant resistance. We investigated this interaction in rice (Oryza sativa L.) and its effect on resistance to the herbivore brown planthopper Nilaparvata lugens (BPH). Our results indicate that high-level (5.76 mM) N fertilization reduced Si accumulation in rice leaves, and furthermore, this decrease was likely due to decreased expression of Si transporters OsLsi1 and OsLsi2. Conversely, reduced N accumulation was observed at high N fertilization levels when Si was exogenously provided, and this was associated with down-regulation of OsAMT1;1 and OsGS1;1, which are involved in ammonium uptake and assimilation, respectively. Under lower N fertilization levels (0.72 and/or 1.44 mM), Si amendment resulted in increased OsNRT1:1, OsGS2, OsFd-GOGAT, OsNADH-GOGAT2 and OsGDH2 expression. Additionally, bioassays revealed that high N fertilization level significantly decreased rice resistance to BPH, and the opposite effect was observed when Si was provided. These results provide additional insight into the antagonistic interaction between Si and N accumulation in rice, and the effects on plant growth and susceptibility to herbivores.